Causal effect of intergroup contact on exclusionary attitudes - Enos, Ryan D (Proceedings of the National Academy of Sciences - PNAS, 2014)
The effect of intergroup contact has long been a question central to social scientists. As political and technological changes bring increased international migration, understanding intergroup contact is increasingly important to scientific and policy debates. Unfortunately, limitations in causal inference using observational data and the practical inability to experimentally manipulate demographic diversity has limited scholars' ability to address the effects of intergroup contact. Here, I report the results of a randomized controlled trial testing the causal effects of repeated intergroup contact, in which Spanish-speaking confederates were randomly assigned to be inserted, for a period of days, into the daily routines of unknowing Anglo-whites living in homogeneous communities in the United States, thus simulating the conditions of demographic change. The result of this experiment is a significant shift toward exclusionary attitudes among treated subjects. This experiment demonstrates that even very minor demographic change causes strong exclusionary reactions. Developed nations and politically liberal subnational units are expected to experience a politically conservative shift as international migration brings increased intergroup contact.